Rancangan reinstalasi runway edge light di bandar udara fransiskus xaverius seda maumere - Nur Aida Basir; Edy Kurniawan; Iwan Koswara (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
The background of this research is the visual landing aid, specifically the runway edge lights, which have experienced an elevation decrease due to repeated overlay work and soil contour conditions. This phenomenon causes the light positions to not meet the ideal elevation thresholds, potentially affecting the effectiveness of visual guidance for pilots during flight operations. The purpose of this research is to produce a technical reinstatement design for the runway lights in accordance with aviation regulations. A Research and Development method was employed through field observations and elevation measurements. The discussion of this research includes an analysis of existing conditions, which serves as the foundation for designing light base height adjustments. The technical design is presented in the Detail Engineering Design (DED) and Bill Off Quantities (BOQ), covering all work aspects, from electrical installation procurement and the calculation of 12,535 meters of FL2XCY primary cable to civil works involving 2,008 m3 of soil excavation, as well as technical specifications for transformer pit construction and runway edge light base reconstruction. The conclusion of this research indicates that reinstatement is essential to restore the optimal function of the lights. The implementation of this design can improve sustainable flight operational safety at Fransiskus Xaverius Seda Maumere Airport.